Dinamika Upaya Inventarisasi Aset Desa di Desa Bungkal Kabupaten Ponorogo - Yusuf Adam Hilman; Khoirurrosyidin Khoirurrosyidin; Robby Darwis Nasution; Aldy Sony Ramadhan; Ahsana Taufiqi Robby; Tirta Nyssa Salsabila (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
Village asset management is an alternative that can be carried out by the village government, to maximize the creation of prosperity for village communities, good asset management, can open business opportunities for village communities, so as to create economically productive activities. This study aims to reveal the extent of the efforts made by the village administration to carry out an inventory of assets. This research uses descriptive qualitative type, using primary and secondary data sources, in the form of interviews and documentation. The informants in this study were the Village Head, Village Secretary and also Village Officials, with a purposive sampling model on the basis that these informants were directly involved actors so that they provided a lot of important information. The results of this study show that the process of inventorying assets does not come from the initiation of the village government, but from the local government and is top down in nature, in carrying out the process it only reaches the reporting process and is only administrative in nature. Apart from that, there are obstacles related to government human resources in charge of asset inventory, so that it has not had much effect on people's welfare.